PEDAGOGICAL VALUES IN THE MAIN CHARACTER OF THE NOVEL SEMESTA CINTA ZAHARA BY FITRIYU SIREGARU - Ridwan; Khoerotun Nisa Liswati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The purpose of this study is to describe the character elements instilled by the characters in the novel Universe of Love Zahara. The type of research used in this study is qualitative research using a descriptive method. The data used in this study is a human instrument, namely the research itself. It can be said that this information and research is all written sources obtained from books and documents of research results. Data sources are divided into two types, namely primary data and secondary data. The primary data is the novel book of the universe of love Zahara, while the secondary data is books, scientific journals, and data related to this research. The results of this study show that Zahara is a hardworking and unyielding figure to achieve his goals. Zahara is also grounded, smart, kind and loves his family. The main character is in the form of Zahara's character in helping.